Comparison of Outcomes of Hemodialysis Adequacy with Dialysate Flow Rate of 500 ml/minute and 650 ml/minute - Leo Ginting; Anggraini Permatasari; Elizsabeth Yasmine; Dheni Koerniawan (The Avicenna Medical Journal, 2021)
Background. The average achievement of hemodialysis adequacy which was carried out twice a week for 4 hours at Fatmawati Hospital was 1.49. As many as 82% had not reached adequate dialysis (Kt/V<1.8). Based on the calculation of the dialysate proportioning system, hemodialysis for 4 hours with a dialysate flow rate/Quick Dialysate Flow (QD) of 500 ml/minute will leave dialysate. In the 1 month observation, there were 1.755.6 liters residual dialysate parts Acid (A) and 6,283.2 liters parts Bicarbonate (B). This residual puts a burden on the hospital in treating liquid waste. But with QD 650 ml/minute, both part A and part B, dialysate is still sufficient. On the other hand, QD can affect the achievement of HD compliance.Aim. Knowing the difference in hemodialysis adequacy with QD 500 ml/minute and 650 ml / minute.Method. This study used a case-control analysis for the control group (QD 500 ml/minute) and the intervention group (QD 650 ml/minute) with a Quasy Experiment design through a comparative analysis approach with matching/cross over techniques. Hemodialysis adequacy (Kt/V) is measured 2 times using the QX calculate application (Daugirdas formula), namely at QD 500 ml/minute and QD 650 ml/minute for further analysis using the Wilcoxon Signed Rank test.Result. The study was conducted on 115 respondents with a total of 230 HD sessions. The mean Kt/V in the intervention group was 1.69 and in the control group 1.49 (p-value = 0.006) and it was seen that there was a shift in the achievement of HD adequacy to a better category; The very inadequate and inadequate adequacy category decreased from QD 500 ml/minute to QD 650 ml/minute, and conversely, the adequate and very adequate adequate category experienced an increase in number.Conclusion. Hemodialysis with QD 650 ml/minute resulted in better hemodialysis adequacy than QD 500 ml/minute.